Clearance of HCV by Combination Therapy of Pegylated Interferon α-2a and Ribavirin Improves Insulin Resistance - Kim, Hong Joo (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Society of Pancreatobiliary Diseases, 2009)
BACKGROUND/AIMS: Chronic hepatitis C virus (HCV) infection is associated with a higher risk of the development of insulin resistance. If HCV is a causal factor for insulin resistance, then clearance of HCV might decrease insulin resistance. The aim of this study was to elucidate the effects of clearance of HCV on insulin resistance. METHODS: We analyzed 28 patients with HCV infection who received combination treatment of 180 µg of pegylated interferon α-2a and ribavirin at our institution from May 2004 to November 2006. Insulin resistance was calculated according to the homeostasis model assessment of insulin resistance (HOMA-IR) method. RESULTS: Twenty-two patients (78.6%) achieved sustained virologic response (SVR), where the fasting plasma glucose level significantly decreased after antiviral treatment. Fasting serum insulin and HOMA-IR also significantly decreased after antiviral treatment, whereas the BMI value was not significantly affected. For the nonresponders (n=6), no significant changes were evident in BMI, fasting plasma glucose, fasting serum insulin, and HOMA-IR at 6 months after the end of antiviral treatment. Logistic regression analysis indicated that the only independent factor contributing to the reduction of insulin resistance was the complete disappearance of HCV RNA at 6 months after the end of antiviral treatment (SVR). CONCLUSIONS: The clearance of HCV by the combination therapy of pegylated interferon α-2a and ribavirin improves insulin resistance by reducing fasting serum insulin and glucose levels.